The economic viability of sustainable paddy farming system: the case from KETARA, IADA, Terengganu - Khairun Nisaa' Mohd Nor
Economic sustainability is one of key elements in sustainable development of Malaysian paddy industry. The aim of this study is to assess the economic viability of sustainable paddy farming system among of the North Terengganu (KET ARA) Integrated Agriculture Development Area (IADA)'s farmers under National Key Economic Area (NKEA) project. The study was conducted by adopting three-tier assessments; perception, farm economic viability (FEV) and macroeconomic level assessment. The perception on ES was obtained through adapted five Point Likertscale questionnaires in which four ES indicators were opted namely safety and quality, financial stability, market and diversification. Using convenience sampling technique, the targeted population included 105 NKEA project rice farmers (Batch 1).The collected data were analysed using a statistical package for social science (SPSS version 19.0) in which descriptive statistics analysis on basis of mean and coefficient variation was performed. Meanwhile, justification on FEV level was assessed based on six indicators; total farm cash receipt, net income, expense to income, return on investment, debt to income and dependency on Government. Thus, long term ES of Malaysian rice farming from a macroeconomic perspective was assessed by reviewing the bottom line of prices and the purchasing power of rice (PPR). Statistical information of time series data on farm harvest price of rice (PR), wholesale commodity price (WP) and rice production (RP) for 42 years period were obtained and compiled from the AGROSTAT system of the Statistical Division of the Food and Agriculture Organization (FAO), the United States Department of Agriculture (USDA), World Bank and the Department of Statistics, Malaysia. The finding shows that the NKEA rice farmers had a high level of perception towards market and financial stability constructs. Dissatisfaction on price of rice produce was ranked first compared to efforts made which was included under the market construct. A total of 82.9% of the respondents exhibit low level of overall justification on their current FEV whereby their justifications were prioritised on the supreme dependency on the Government. At the macroeconomic level, the outcome reveals that PPR or 'real rice' was only 61% of that in 1972, A drop of 39% of its purchasing power. Overall, economic viability of rice farming among of the selected farmers was still unsatisfactory due to supreme dependency on Government and low price of real rice produce.